Elementy wyposażenia wnętrz świątyń cystersów w XVI i pierwszej połowie XVII wieku .......... 311 - Barczyński, Roman (Dzieje i kultura Cystersów w Polsce, 2025)
INTERIOR FURNISHING ELEMENTS OF CISTERCIAN TEMPLES IN THE 16TH AND FIRST HALF OF THE 17TH CENTURYAmong the numerous artifacts made in the 16th and the first half of the 17th century in the circle of Silesian Cistercians, few have survived to our times. Among them, several sculptures, a retable section, a polyptych from the beginning of the 16th century, and a painting from the second half of the 16th century have been preserved. The largest number of preserved works of art dates from the beginning of the 17th century, these are the chalices, paintings and triptych. A typical feature of all artifacts made in both renaissance and mannerist styles is their eclecticism with the gothic style. The artifacts created in the Renaissance era are characterized by use of harmonious forms; balanced, geometrically calculated compositions. Characteristic for works created in the era of Dutch mannerism is the use of the composition Figura serpentinata, a desire to use combinations of artificial colors. The mannerist works are also characterized by the use of inscriptions on their surface, they were to be used to correctly read the content of artistic scenes or manifest the ideological thoughts of the founders.